So, I'm supposed to use product of infinite series methods to find the series for $(\ln(1+z))^2$. I'm given that the answer has the form $$z^2 \sum_{l=0}^{\infty} c_l z^l$$ and I'm given that the first few terms are $$z^2-\left(1+\frac{1}{2}\right)\frac{2z^3}{3}+\left(1+\frac{1}{2}+\frac{1}{3}\right)\frac{2z^4}{4}-...$$

One can easily see that $c_l$ should be $\sum_{n=0}^{l}(-1)^l\frac{2}{(n+1)(l+2)}$, but I'd like to find this by working forward from the series rather than backward from its terms.

I start by squaring the series for $\ln(1+z)$: $$\left(\sum_{n=0}^{\infty}(-1)^n\left(\frac{z^{n+1}}{n+1}\right)\right) \left(\sum_{m=0}^{\infty}(-1)^m\left(\frac{z^{m+1}}{m+1}\right)\right)=\sum_{n=0}^{\infty}\sum_{m=0}^{\infty}(-1)^{n+m}\frac{z^{n+m+2}}{(n+1)(m+1)}\\=\sum_{l=0}^{\infty}\sum_{n=0}^{l}(-1)^{l}\frac{z^{l+2}}{(n+1)(l-n+1)}$$ where $l=n+m$.

This incorrectly suggests $c_l=\sum_{n=0}^l \frac{(-1)^l}{(n+1)(l-n+1)}$.

If anyone could spot my error, I would be very grateful.

  • $\begingroup$ There is no error, you just need a small extra trick to convert your formula into the given one. $\endgroup$ – Jack D'Aurizio Jul 31 '15 at 21:15

It is more practical to find the Taylor series of $\log^2(1-z)$, then replace $z$ with $-z$. Since:

$$ \log(1-z)=\sum_{n\geq 1}\frac{z^n}{n} $$ we have: $$ \log^2(1-z) = \sum_{n\geq 2}\left(\sum_{k=1}^{n-1}\frac{1}{k(n-k)}\right)z^n $$ but: $$ \frac{1}{k(n-k)}=\frac{1}{n}\left(\frac{1}{k}+\frac{1}{n-k}\right)$$ hence: $$ \log^2(1-z) = \sum_{n\geq 2}\frac{2 H_{n-1}}{n} z^n $$ where $H_m=\sum_{j=1}^{m}\frac{1}{j}$. That leads to:

$$ \log^2(1+z) = \sum_{n\geq 1}\frac{2(-1)^n H_{n-1}}{n} z^n.$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.